Benzimidazole fungicides are detrimental to common farmland ants. (May 2018) - Heneberg, Petr; Svoboda, Jakub; Pech, Pavel
Abstract: The impacts of pesticides on biodiversity of off-target organisms are neglected, and current conservation strategies pay little attention to these issues. Particularly the sublethal effects of chemical compounds used in agriculture and forestry are poorly understood, despite they may have detrimental effects on populations of the affected off-target organisms. Here, we tested the effects of 11 benzimidazole fungicides. Benzimidazole fungicides are still being widely used as broad-spectrum plant fungicides in agriculture since 1960s. We tested their effects on the fecundity and survival of queens of Myrmica rubra, a common farmland ant species, following the oral administration of the fungicides for a period of six weeks. We found that ethanolic solutions, as well as water suspensions of all but one tested benzimidazole fungicides, inhibited significantly the fecundity of M. rubra queens; in addition, the flusilazole was lethal when administered at 1.0 and 0.1 mg ml −1 . Combined data suggest that the whole class of benzimidazole fungicides has detrimental sublethal effects on the tested ant species and substantially decrease the fitness of the study species. The fact that common farmland species suffer from the effects the application of any of the whole class of fungicides questions their currently widespread use as agricultural fungicides. These findings bring into question the safety of agricultural benzimidazole fungicides and we recommend that their routine spraying should be re-assessed by regulatory agencies. Graphical abstract: Unlabelled Image Highlights: Conservation implications of pesticides' impacts are insufficiently recognized. Benzimidazole fungicides are massively used in agriculture for over five decades. Benzimidazole fungicides are detrimental to common farmland ants. All but one benzimidazole fungicides inhibited the fecundity of M. rubra queens. Flusilazole was lethal to M. rubra queens when administered at 100 μg/ml p.o.